Analisis Corporate Social Responsibility (CSR) dan Green Human Resources Management pada PT Batam Plastik - Antony Sentoso; Nicholas Nicholas; Tan Phey Lien; Jesslyn Larissa; Selvia Eka Marliana; Richmond Richmond; Joven Alfando Cang (Universitas 17 Agustus 1945 Semarang, 2023)
The plastic manufacturing industry in Indonesia has become a much needed industry because consumption power continues to rise. One company in Batam that produces plastic is PT Batam Plastik. As a plastic factory, PT Batam Plastik will add plastic waste that cannot be broken down in Batam City. This article was created to analyze the Corporate Social Responsibility (CSR) program and green human resource management at PT Batam Plastik. This type of qualitative research uses data collection techniques using interview and observation techniques. Based on the results of the analysis that has been carried out, PT Plastik Batam has implemented the Corporate Social Responsibility (CSR) program and environmentally friendly human resource management correctly. This is based on data from interviews conducted where PT Plastik Batam recycles plastic waste into recycled products and has trained its employees on how to recycle plastic and reuse plastic.